Strengthening the Capacity of Village Equipment through Administrative Training and Criteria in Pernek Village, Moyo Hulu District - Hendra Gunawan; Wiwik Surya Utami; Jumianti Dianai (Peneliti Teknologi Teknik Indonesia, 2022)
The purpose of this service is to provide understanding and improve the abilities of Pernek Village officials in composing correspondence and activity proposals. This is done because so far errors are still often found in preparing letters and making activity proposals. However, because it was demanded by the duties and responsibilities of the service in Pernek Village, these mistakes were considered normal. Therefore, we, from the Sumbawa University of Technology, collaborated with the Pernek Village government to provide training as contained in the theme of this service activity, namely Strengthening the Capacity of Village Officials Through Administrative Training and Correspondence in Pernek Village, Moyo Hulu District. The methods of implementation in this service are lectures, discussions, questions and answers, group and individual assignments. The results of the implementation of this activity, namely, the formation of village staff who have the ability to compose correspondence without having to rely on copying and pasting existing letters. In addition, Pernek Village staff can be independent in compiling activity proposals, budget proposals, and other proposals, which are usually carried out by other people outside of Pernek Village staff.